2003
DOI: 10.1021/ol035288m
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Silylation of Aryl Bromides Leading to Functionalized Aryldimethylsilanols

Abstract: [reaction: see text] A mild and general palladium-catalyzed insertion of 1,2-diethoxy-1,1,2,2-tetramethyldisilane into a variety of aryl bromides affords the aryldimethylsilyl ethers in high yields. Hydrolysis of the ethers under pH-optimized conditions results in the exclusive formation of the desired aryldimethylsilanols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…Another method is the catalytic conversion of C-H bonds to C-Si bonds in the presence of transition-metal complexes [5,6]. Different research groups separately reported on the transition-metal-catalyzed coupling reaction of aryl halides with trialkoxysilanes [7][8][9][10][11]. Although, trialkylsilanes (e.g., Et 3 SiH) have not been found suitable silylating agent in some catalytic systems [12], recently, their use to attain the silylation of aryl halides under Pd and Pt catalysis have been reported [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Another method is the catalytic conversion of C-H bonds to C-Si bonds in the presence of transition-metal complexes [5,6]. Different research groups separately reported on the transition-metal-catalyzed coupling reaction of aryl halides with trialkoxysilanes [7][8][9][10][11]. Although, trialkylsilanes (e.g., Et 3 SiH) have not been found suitable silylating agent in some catalytic systems [12], recently, their use to attain the silylation of aryl halides under Pd and Pt catalysis have been reported [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The silyl group must withstand the conditions of the heteroannulation and then undergo hydrolysis to the silanol with out protodesilylation under mild conditions 33. Thus, 1-heptyne was lithiated and the lithioalkyne trapped with dimethyl chlorosilane to afford silyl hydride 9 in 70% yield (Scheme 2, eq.…”
Section: Resultsmentioning
confidence: 99%
“…First, the development of an alkynyl silyl ether that is stable under the heteroannulation conditions, but easily cleaved without protodesilylation posed a difficult challenge. This challenge is particularly important in light of studies that demonstrated that silyl ethers can be cleaved under basic conditions33 and premature release of the silanol could lead to undesired side products. Furthermore, the cross-coupling of (2-indolyl)silanols bearing a substituent at the C(3) position has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…3). 25 For effective reaction with aryl bromides, a bulky electron-rich phosphine (JohnPhos) 26 is required. The pH of the workup is critical to suppress formation of the disiloxane.…”
Section: Silanolsmentioning
confidence: 99%